2011
DOI: 10.1007/s00264-011-1289-4
|View full text |Cite
|
Sign up to set email alerts
|

Primary total hip arthroplasty with dual mobility socket to prevent dislocation: a 22-year follow-up of 240 hips

Abstract: Purpose The longest follow-up dual mobility series from inventor Gilles Bousquet focussing on implant survival and the incidence of dislocation. Methods This was a retrospective study from 1985 to 1990, on 240 hips using a PF® modular femoral stem and a dual mobility Novae® tripodal socket (SERF). Results The 22-year follow-up global survival rate was 74%. No dislocation occurred, 41 hips were revised, including ten retentive failures (RF), 12 hips were lost to follow-up, 87 patients (99 hips) died without rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
136
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 191 publications
(142 citation statements)
references
References 23 publications
3
136
0
3
Order By: Relevance
“…Moreover, Epinette et al [11] analyzed 437 primary cemented THAs and noted a 100% cup survivorship for patients younger than 70 years of age and 99.7% for patients older than 70 years of age at minimum 2-year followup. Similar to our study, Boyer et al [6] reported a final followup mean HHS of 92 (SD, 1.9) in their retrospective study of 240 hips with a minimum followup of 18 years. Bauchu et al [3] also reported an improvement in the mean Postel-Merle d'Aubigne score (from 9 to 17) in their study of 150 dual-mobility hips.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Moreover, Epinette et al [11] analyzed 437 primary cemented THAs and noted a 100% cup survivorship for patients younger than 70 years of age and 99.7% for patients older than 70 years of age at minimum 2-year followup. Similar to our study, Boyer et al [6] reported a final followup mean HHS of 92 (SD, 1.9) in their retrospective study of 240 hips with a minimum followup of 18 years. Bauchu et al [3] also reported an improvement in the mean Postel-Merle d'Aubigne score (from 9 to 17) in their study of 150 dual-mobility hips.…”
Section: Discussionsupporting
confidence: 91%
“…At 7 years, the proportion of cup survivorship was 97%. Similarly, Boyer et al [6] analyzed 240 cementless dual-mobility hips and found no dislocations with 80% cup survivorship at a minimum followup of 18 years. Furthermore, Guyen et al [15] performed a study on 167 dual-mobility hips and reported no dislocations at a minimum followup of 2 years with a 5-year cup survivorship proportion of 96%.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations